A randomized, placebo‐controlled, dose‐escalation phase I/II multicenter trial of low‐dose cidofovir for BK polyomavirus nephropathy - Imlay, Hannah; Gnann, John W.; Rooney, James; Peddi, V. Ram; Wiseman, Alexander C.; Josephson, Michelle A.; Kew, Clifton; Young, Jo‐Anne H.; Adey, Deborah B.; Samaniego‐Picota, Milagros; Whitley, Richard J.; Limaye, Ajit P. (Transplant infectious disease, 2024)
Background BK polyomavirus‐associated nephropathy (BKPyVAN) is an important cause of allograft dysfunction and failure in kidney transplant recipients (KTRs) and there are no proven effective treatments. Case reports and in vitro data support the potential activity of cidofovir against BK polyomavirus (BKPyV). Methods We report the results of a phase I/II, double‐blind, placebo‐controlled randomized dose‐escalation trial of cidofovir in KTRs with biopsy‐confirmed BKPyVAN and estimated glomerular filtration rate ≥30 mL/min. Intravenous cidofovir (0.25 mg/kg/dose or 0.5 mg/kg/dose) or placebo was administered on days 0, 7, 21, and 35, with final follow‐up through day 49. Results The trial was prematurely discontinued due to slow accrual after 22 KTRs had completed the study. Cidofovir was safe and tolerated at the doses and duration studied. The proportion of subjects with any adverse event (AE) was similar between groups (9/14 [64%] in the combined cidofovir dose groups and 6/8 [75%] in the placebo group); 84% of AEs were mild. BKPyV DNAemia reduction by day 49 was similar between groups (>1 log10 reduction in (2/9 [22.2%] of 0.25 mg/kg group, 1/5 [20%] of 0.5 mg/kg group, and 2/8 [25%] of placebo group). Conclusions These preliminary results indicate that low‐dose cidofovir was safe and tolerated but had no significant BKPyV‐specific antiviral effect in KTRs with BKPyVAN. In a randomized, placebo‐controlled, dose‐escalation phase I/II multicenter trial of low‐dose cidofovir for BK polyomavirus nephropathy, cidofovir was found to be safe and tolerated but demonstrated no significant BK polyomavirus‐specific antiviral effect.